Characteristics of construction firms at risk for future workers' compensation claims using administrative data systems, Washington State. (June 2018) - Marcum, Jennifer L.; Foley, Michael; Adams, Darrin; Bonauto, Dave
Abstract: Introduction: Construction is high-hazard industry, and continually ranks among those with the highest workers' compensation (WC) claim rates in Washington State (WA). However, not all construction firms are at equal risk. We tested the ability to identify those construction firms most at risk for future claims using only administrative WC and unemployment insurance data. Methods: We collected information on construction firms with 10–50 average full time equivalent (FTE) employees from the WA unemployment insurance and WC data systems (n = 1228). Negative binomial regression was used to test the ability of firm characteristics measured during 2011–2013 to predict time-loss claim rates in the following year, 2014. Results: Claim rates in 2014 varied by construction industry groups, ranging from 0.7 (Land Subdivision) to 4.6 (Foundation, Structure, and Building Construction) claims per 100 FTE. Construction firms with higher average WC premium rates, a history of WC claims, increasing number of quarterly FTE, and lower average wage rates during 2011–2013 were predicted to have higher WC claim rates in 2014. Conclusions: We demonstrate the ability to leverage administrative data to identify construction firms predicted to have future WC claims. This study should be repeated to determine if these results are applicable to other high-hazard industries. Practical Applications: This study identified characteristics that may be used to further refine targeted outreach and prevention to construction firms at risk.